(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Agreen house <’xperiment was designed to investigate the effect of soil salinity and gibberellic acid (GA3) on the leaf contertof nucleic acid. Seeds of Lea mays L. (synthetic variety) were soaked seperately for 24 hr. in 50, 100 and 2ilil ppm solution of gibberellic acid (GA3) while seeds which were soaked in distilled water served as control.